VD_FINDINFO HC / 2016 / 231 vom 3. März 2016 - VD Tribunal cantonal (2016)
CAS CLAIR, COURTAGE, VENTE D'IMMEUBLE, CONDITION RÉSOLUTOIRE, CONDITION SUSPENSIVE | 151 CO, 154 CO, 18 al. 1 CO, 413 al. 2 CO, 85a LP, 257 CPC (CH)